2010
DOI: 10.1021/pr100710g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteome and Acidic Subproteome Profiling of Candida albicans Yeast-to-Hypha Transition

Abstract: Candida albicans yeast-to-hypha morphological transition is involved in the virulence strategy of this opportunistic fungal pathogen. Changes in relative abundance of the Candida proteome related to this process were analyzed using different two-dimensional differential in-gel electrophoresis (2D-DIGE)-based approaches. First, a comparative analysis of yeast and hyphal cytoplasmic proteins allowed the detection of 106 protein spots with significant variation in abundance. Sixty-one of them, corresponding to 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 58 publications
5
35
0
Order By: Relevance
“…18S rRNA was used as reference gene Carbohydrate pathway Proteomic analysis showed a different organisation of the carbohydrate pathway in the two morphologies. Several proteins, belonging to glycolysis/gluoconeogenesis pathway, increased in abundance in yeast morphology of P. fermentans as a consequence of the exponential growth phase of the yeast form, and in accordance with data reported by Monteoliva et al (2011). This behaviour suggests that the yeast status is characterised by active aerobic glycolysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…18S rRNA was used as reference gene Carbohydrate pathway Proteomic analysis showed a different organisation of the carbohydrate pathway in the two morphologies. Several proteins, belonging to glycolysis/gluoconeogenesis pathway, increased in abundance in yeast morphology of P. fermentans as a consequence of the exponential growth phase of the yeast form, and in accordance with data reported by Monteoliva et al (2011). This behaviour suggests that the yeast status is characterised by active aerobic glycolysis.…”
Section: Discussionsupporting
confidence: 90%
“…This behaviour might indicate that different species of the same protein might be involved in the dimorphic transition with different physiological relevance in the two morphologies (Jungblut et al 2008;Schlüter et al 2009). In Candida albicans, Monteoliva et al (2011) suggested that phosphoglycerate mutase can function as glycolytic enzyme providing energy for the yeast growth morphology, whereas in the filamentous growth, phosphoglycerate mutase might provide glucose donor for the synthesis of β-glucans and chitin. Further investigations should be performed to understand the function of different protein species in the transition of P. fermentans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other proteins in the FBS series showed moderate abundance changes [19]. Based on these results, we suggest that C. albicans employed the following adaptation strategy: first, C. albicans tuned its proteome to adapt to a new environment, in which most proteins were upregulated 2-fold higher than has been suggested by previous studies [23]. Second, a few proteins were upregulated >5-fold, which might suggest that these proteins were critical for adaptation to the novel environment.…”
Section: Quantitative Time-course Proteomicssupporting
confidence: 57%
“…In-solution digestion was performed as reported elsewhere (36). Proteins were reduced with 5 mM DTT for 30 min at 37°C and alkylated with 10 mM iodoacetamide for 30 min at 30°C.…”
Section: Sds-page Separation Andmentioning
confidence: 99%